The impact of the Jigsaw cooperative learning model on creative thinking and collaboration in fifth-grade natural and social sciences - Tara, Leri; Firdaus, Fery Muhamad (Jurnal Penelitian Ilmu Pendidikan, 2025)
This classroom action research (CAR) aimed to investigate the impact of the Jigsaw cooperative learning model on fifth-grade students' creative thinking and collaboration skills in Natural and Social Sciences. Conducted over two cycles at SD Negeri Baturetno in the 2024/2025 academic year, the study involved 12 fifth-grade students. Data were collected through a creative thinking test and a validated collaboration observation sheet. The findings demonstrated significant improvements in both domains. Students' active collaboration increased from 66.7% in the first cycle to 91.7% in the second, while lesson implementation completeness reached 100%. The average score on the creative thinking test rose from 72.5 to 81.25, and the percentage of students achieving mastery increased from 75% to 91.7%. Improvements were observed across all indicators: fluency, flexibility, originality, and elaboration in creative thinking, as well as effective communication, respect for others' opinions, and conflict resolution in collaboration. The study concludes that the Jigsaw model is an effective and innovative pedagogical strategy for enhancing meaningful and collaborative learning in elementary school settings.